Tea Polyphenols Improve Down-Regulation of Mitochondrial Functional Gene Expression Induced by Bisphenol A in Zebrafish Ovaries - Dai, Xiaoxin; Qiu, Lijun; Zhang, Han; Xu, Chunying; Zhao, Bo; Gao, Yang; Li, Haidong; Mu, Yi; Chu, Zhangjie (Frontiers in Marine Science, 2022)
The plasticizer bisphenol A, a typical endocrine disrupting chemical, is widely present in the environment. Previous studies demonstrated that exposure to bisphenol A can cause reproductive toxicity, abnormal fertilization, and infertility. However, the mechanisms of low-concentration bisphenol A on the reproductive system and treatment measures have not been fully determined. In this study, we explored the transcriptomic profiles of female zebrafish ovaries. The transcriptomic data revealed that mitochondrial NADH dehydrogenase (mt-Nd) genes were significantly decreased in the bisphenol A-exposed group, while the co-administration of tea polyphenols remarkably elevated the expression of mt-Nd genes. To further explore the expression pattern of the mt-Nd, we analyzed the expression of six mt-Nd genes on different days by qRT-PCR in control, bisphenol A-exposed, and bisphenol A-tea polyphenols ovaries. Here, we found that 0.1 mg/L bisphenol A exposure adversely affects the mitochondrial respiratory chain in ovaries and may lead to reproductive disorders. Finally, our study demonstrated that tea polyphenols play a protective role in ovarian mitochondrial dysfunction in low-concentration bisphenol A-exposed female zebrafish.